Intelligence Management and its impact on Security Architecture in Karu Local Government Area of Nasarawa State, Nigeria - Obi, E. Nku (NIU Journal of Social Sciences; Vol 9 No 2 (2023): NIU Journal of Social Sciences, Vol. 9 No. 2, June 2023, 2023)
This study examines Intelligence Management and Its Impact on the Security Architecture in Karu Local Government Area of Nasarawa State, Nigeria. Primary data were derived from questionnaires and in-depth interviews with the Department of State Security Service, Defense Intelligence Agency, Nigerian Intelligence Agency, Force Intelligence Bureau, the Joint Intelligence Board, Office of the National Security Adviser, other security agencies like the Customs, Immigration, NSCDC, Prisons, NDLEA and other stakeholders. The system theory was adopted which holds that security architecture is made up of sub-systems, and when these sub-systems function properly, the system as a whole function well, but if one part is affected, it can impact on others. However, it was revealed that the similarities in the statutory roles of the various security agencies had made it difficult to demarcate their constitutional responsibilities, which often culminates in clashes between different personnel on various security issues rather than a joined-up approach to fighting crime in a joint security operations and the politicization of intelligence management had impacted negatively on the security architecture which has made recruitment easy for other forms of criminalities as they capitalize on the political situations of the country. Despites the provisions within the Intelligence Services Act 2001, the government is yet to appoint an ombudsman and standards unit for the intelligence agencies which will ensure it remains in compliance with Nigeria's democratic tenets. Therefore, the paper recommends that the Nigeria government should develop a mechanism capable of harmonizing the various agencies and enlighten them on the need to place national security above every other issues. In addition, the decision making's reaction to available intelligence is often slow and sometimes uncoordinated; hence, intelligence operations need to be better coordinated, more robust and where possible, decentralized to identify potential threats within localities. Keywords: Intelligence Management, Security, and Security Architecture